ANALYSIS OF DETERMINANTS THAT INFLUENCE THE VOLUME OF INDONESIAN SHRIMP EXPORTS TO MAIN DESTINATION COUNTRIES FOR THE 2013-2022 PERIOD - Ni Kadek Anggita Dwi Cahyani; Putu Krisna Adwitya Sanjaya (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Among several superior marine and fisheries commodities owned by Indonesia, shrimp is one of the superior commodities that has quite large potential. This potential has not been utilized properly, even though shrimp is currently a commodity that has high economic value. Problems related to the condition of Indonesia's export volume tend to fluctuate, this is very important to pay attention to in order to find out the determinants that influence the increase and decrease in the volume of Indonesian shrimp exports to destination countries. The aim of this research is to analyze the simultaneous and partial influence of GDP per capita, population, inflation rate and US dollar exchange rate on the volume of Indonesian shrimp exports to the main destination countries for the 2013-2022 period. The analysis technique used is a panel data regression model with 70 observations obtained through secondary data. The model chosen is the FEM model and the classical assumption tests used are the multicollinearity test and heteroscedasticity test. The results of this research, namely GDP per capita and the inflation rate have a positive but not significant effect on the volume of Indonesian shrimp exports to the main destination countries in 2013-2022, population has a positive and significant effect on the volume of Indonesian shrimp exports to the main destination countries in 2013-2022 , the dollar exchange rate has a negative and significant effect on the volume of Indonesian shrimp exports to the main destination countries in 2013-2022.